Effect of Personal Selling on Consumer Impulse Buying Behaviors: Evidence from Selected Quoted Foods and Beverages Firms in Nigeria (Global Journal of Management and Business Research, 2019)
Consumer's needs are multi-variants, divergent and insatiable. The best communication strategies to get target audience and consumers attention become a serious challenge. This study examined the effect of Personal selling (PS) on Consumer Impulse Buying Behaviour (CIBB) this study makes use of a structured questionnaire which was administered in southwestern states of the country. Descriptive analyses, linear regression, and ANOVA were used to analyze the data. With 0.005% level of significance. The study revealed that personal selling has a significant impact on consumer's impulse buying behavior. Therefore, an organization should implement the best strategy as a competitive advantage in presenting their offering.
Keywords: personal selling; marketing; consumer; buying behaviour; strategy